2020
DOI: 10.1371/journal.pone.0240806
|View full text |Cite
|
Sign up to set email alerts
|

Smoking cessation and related factors in middle-aged and older Chinese adults: Evidence from a longitudinal study

Abstract: Objectives There are more than 300 million smokers in China. This study aimed to evaluate the rate of smoking cessation, smoking relapse and related factors in middle-aged and older smokers in China. Methods We performed a secondary analysis of data from China Health and Retirement Longitudinal Study (CHARLS) that recruited a nationally representative sample of adults aged 45 and older. Participants were 3708 smokers in 2011 who completed two waves of follow-up interviews in 2013 and 2015. Self-reported quit a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 21 publications
(30 reference statements)
2
23
1
Order By: Relevance
“…It is a nationally representative longitudinal survey that collected information on Chinese residents aged 45 years and above and their spouses regarding assessments of social, economic and health circumstances. To ensure cross-study comparability of the results, the CHARLS was harmonised with leading international research studies in the Health and Retirement Study (HRS) and intended to provide a high-quality public microdatabase with a wide range of information that serves the needs of scientific and policy research on ageing-related issues 24…”
Section: Methodsmentioning
confidence: 99%
“…It is a nationally representative longitudinal survey that collected information on Chinese residents aged 45 years and above and their spouses regarding assessments of social, economic and health circumstances. To ensure cross-study comparability of the results, the CHARLS was harmonised with leading international research studies in the Health and Retirement Study (HRS) and intended to provide a high-quality public microdatabase with a wide range of information that serves the needs of scientific and policy research on ageing-related issues 24…”
Section: Methodsmentioning
confidence: 99%
“…All enrollees were notified, and informed consent was obtained before the interviews. We applied to the CHARLS team for data for this study and received anonymous enrollees ( 19 ).…”
Section: Methodsmentioning
confidence: 99%
“…The current study shows that older age and the absence of underlying diseases are not significant factors associated with successfully quitting smoking. In contrast, a largescale study in China found that older age was associated with higher odds of smoking abstinence [24]. Meanwhile, Joly et al found that smoking-related diseases do not facilitate smoking cessation or the maintenance of abstinence, as smokers with comorbidities may be discouraged from stopping since the diseases have already occurred [25].…”
Section: Discussionmentioning
confidence: 98%
“…All medical records of adult smokers (age ≥ 18 years old) who were prescribed varenicline as pharmacotherapy for smoking cessation between January 2017 and June 2018 were traced. The medical records (including abstinence and adverse events) were traced according to the quit smoking clinic visits schedule, at a bi-weekly time-point during the first 12 weeks (Week-2, 4, 6, 8, 10, 12) and four-weekly thereafter 20,24). Medical records of smokers who used pharmacotherapy other than varenicline for smoking cessation, of those who received less than four weeks of varenicline treatment, and of those who had missing data were excluded.…”
Section: Study Design and Populationmentioning
confidence: 99%